INCREASING THE EMPLOYEES’ PERFORMANCE THROUGH TRANSFORMATIONAL LEADERSHIP AND ORGANIZATIONAL CULTURE AT PT. PERKEBUNAN NUSANTARA V RIAU - Marnis Marnis (Journal of Economics, Business, and Accountancy Ventura, 2013)
The research is conducted at PT. Perkebunan Nusantara V (PTPN V) Riau. It has some objectivessuch as to examine and analyze (1) the effect of transformational leadership and organizationalculture on employee performance, (2) the effect of transformational leadershipand organizational culture on organizational commitment, and (3) the effect of organizationalcommitment on employee performance. The population taken consists of 146 peoplecovering middle managers. The sampling was done by means of census on the entire population.The testing and analysis of the data was done by using structural equation modeling(SEM) with AMOS 7 program. The results indicate that transformational leadership and organizationalculture have a positive and significant effect of employee performance. In addition,the transformational leadership and organizational culture also have a positive andsignificant effect on the organizational commitment. In general, it provides evidence that theorganizational commitment and significant positive have effect on employee performance.